Effet prononcé du stretching passif sur la performance dans les sports à dominante force et vitesse. (Cas du football) - Mokkedes Moulay Idriss (My University, 2015)
Pronounced effect of passif stretching on performance in sports dominant strength and speed Mokkedes Moulay Idriss1 1 Sciences of sport training department, Sports and Physical Education Institute, Abdel amid Ibn Badis University, Mostaganem,Algeria. The objective of the present study was to investigate the effects of passif stretching alone on subsequent agility, sprinting, and jump performance. two different stretching protocols: (a) static stretch (SS) to point of discomfort (POD); (b) a control warm-up condition without stretching were implemented with a prior aerobic warm-up and followed by dynamic activities. Dependent variables included a 10-m and 30-m sprint, agility run, VMA, jump and measure of flexibility tests. The control condition showed significant differences (p = 0.05) for sprint, agility run, VMA, jump and measure of flexibility tests faster than the PS,POD condition. There were variable effects during the four phases of play .The performances were effected during the first time (D1) ,muscular capacities recuperation in the second (D2),significate progresses in the theired (D3) and stability with some perturbation in the last (D4). The lack of stretch-induced impairments may be attributed to the trained state of the participants or the amount of time used after stretching before the performance. Participants were either amators or régional level football athlets who trained 3–4 times a week with each session lasting ;90 minutes. Based on these findings and the literature, trained individuals who wish to implement static stretching should include an adequate warm-up and dynamic sport- specific activities with at least 5 or more minutes of recovery before their sport activity.
Keywords: passif stretching, football performance, pronounced effects